Access to Stable Quaternary Phosphiranium Salts by P-Alkylation and P-Arylation of Phosphiranes - Gasnot, Julien; Botella, Clément; Comesse, Sébastien; Lakhdar, Sami; Alayrac, Carole; Gaumont, Annie-Claude; Dalla, Vincent; Taillier, Catherine (Synlett, 2020)
We report the preparation of phosphiranium salts by quaternarization of phosphiranes, a class of sensitive, highly strained, and poorly nucleophilic cyclic phosphines. High-yielding introduction of a varied set of alkyl groups including methylene ester arms was accomplished under mild conditions. A Cu-catalyzed electrophilic arylation of phosphiranes using diaryl iodonium reagents was also achieved to yield unprecedented P,P-diaryl phosphiranium salts with good efficiency.
Keywords: alkylation; arylation; phosphirane; phosphiranium salt; alkylating agent; diaryliodonium salt